Mobile Information Literacy - Matula, Kamil (Qualitative and Quantitative Methods in Libraries; Vol 9 No 4 (2020): December Issue 2020, 2021)
The growing trend of using mobile devices to access and deliver information are forcing us to adapt information services and digital content for mobile devices. Users who connect to the internet and services via mobile devices look forward to possibilities of seeking, processing, saving, sharing and delivering information through variety of smart devices and to have access to information anywhere and anytime. The mobile information literacy is presented as a theoretical concept based on well known concepts of computer, information and digital literacies, especially on the newest definition of information literacy provided by CILIP (2018) which is compared to best practices and TASCHA (2015) curriculum of Mobile Information Literacy. Skills and abilities to discover, seek, process, and use information ethically may be different in mobile environment due to differences how people handle mobile devices, attributes of devices, and basics of our information behaviour on the move than in interaction with computer.